DOES THE NIAS TRIBE'S HEAD CIRCUMFERENCE CORRELATE WITH BODY HEIGHT? - Windy Juwita Lumbanraja; Saharnauli Janna Verawaty Simorangkir; Joseph Partogi Sibarani (Universitas Airlangga, Surabaya, Indonesia, 2024)
Highlights A significant correlation was found between head circumference and height among Nias tribe students. This study was conducted to obtain formulations on weight determination based on headbands in the Nias tribe. Abstract Background: Anthropometric measures are one of the protocols frequently employed to identify deceased bodies. Height, age, and gender are a few anthropometric traits that might be utilized to identify the victim from the corpse. If body components are absent, head circumference can be used to determine body height. Objective: The goal of the study was to ascertain whether there is a correlation between head circumference and body height by gender and to create formulas for estimating weight based on head circumference in the Nias tribe at the University of HKBP Nommensen Medan, Indonesia. Material and Method: The study was conducted from September to October 2023 at the University of HKBP Nommensen using an observational cross-sectional design. Of the 100 students who met the inclusion criteria, 50 were men, and the remaining 50 were women. The study's dependent variable was micro-toise-measured height. The head circumference, expressed in meters of tape, served as the study variable. Result: Statistical analysis of the study results from a significant correlation between the head circumference and the height (r = 0.655, p<0.01). The linear regression equation obtained was y = 3200 x - 2.672 in men and y = 10970 + 2.728 times in women, where y was height and x was head circumference. Conclusion: A substantial height-head circumference association was found among the Nias tribe at the University of HKBP Nommensen Medan, Indonesia. The identification method of the forensic field may benefit from this research.